Functional inhibition of chemokine receptor CCR2 by dicer-substrate-siRNA prevents pain development - Bégin-Lavallée, Valérie (Mol Pain, 2016)
BACKGROUND: Accumulating evidence suggests that the C-C chemokine ligand 2 (CCL2, or monocyte chemoattractant protein 1) acts as a neuromodulator in the central nervous system through its binding to the C-C chemokine receptor 2 (CCR2). Notably, it is well established that the CCL2/CCR2 axis plays a key role in neuron-glia communication as well as in spinal nociceptive transmission. Gene silencing through RNA interference has recently emerged as a promising avenue in research and drug development, including therapeutic management of chronic pain. In the present study, we used 27-mer Dicer-substrate small interfering RNA (DsiRNA) targeting CCR2 and assessed their ability to reverse the nociceptive behaviors induced by spinal CCL2 injection or following intraplantar injection of complete Freund’s adjuvant. RESULTS: To this end, we first developed high-potency DsiRNAs designed to target different sequences distributed across the rat CCR2 (rCCR2) messenger RNA. For optimization, methyl groups were added to the two most potent DsiRNA candidates (Evader and M7 2′-O-methyl modified duplexes) in order to improve in vivo duplex stability and to reduce potential immunostimulatory activity. Our results demonstrated that all modified candidates formulated with the cell-penetrating peptide reagent Transductin showed strong RNAi activity following intrathecal delivery, exhibiting >50% rCCR2 knockdown in lumbar dorsal root ganglia. Accordingly, we found that these DsiRNA duplexes were able to reduce spinal microglia activation and were effective at blocking CCL2-induced mechanical hypersensitivity. Along with similar reductions of rCCR2 messenger RNA, both sequences and methylation patterns were similarly effective in inhibiting the CCL2 nociceptive action for the whole seven days testing period, compared to mismatch DsiRNA. DsiRNAs against CCR2 also reversed the hypernociceptive responses observed in the complete Freund’s adjuvant-induced inflammatory chronic pain model. CONCLUSION: Altogether, these results validate CCR2 as a an appropriate molecular target for pain control and demonstrate that RNAi-based gene therapy represent an highly specific alternative to classical pharmacological approaches to treat central pathologies such as chronic pain.